UJI EFEKTIVITAS TEKNIK RELAKSASI, SENAM POMPA JANTUNG DAN PENGUATAN OTOT PERUT TERHADAP PENURUNAN NYERI MENSTRUASI - Fitriahadi, Enny (MEDIA ILMU KESEHATAN, 2016)
Background: Dysmenorrhea is menstruation pain commonly experienced by female adolescents. This problem is caused by progesterone imbalance in the blood, prostaglandins and stress/psychology factors. It affects on at least 50% of women in reproductive age and 60-85% of female teenagers. Objective: This study aimed to investigate the effectiveness of relaxation techniques, heart pump exercise and strengthening the abdominal muscles to decrease menstrual pain in the second semester students of STIKES 'Aisiyah Yogyakarta in 2015. Methods: This was quantitative research with quasy experimental design with nonequivalent control group. Samples were selected using simple random sampling. The samples in this study were 60 female students. Analysis of the data used Kendall’s Tau. Result: The findings showed that relaxation techniques together with heart pumping exercises provide lower effectiveness in reducing menstrual pain with p-value of 0.059. Whereas, relaxation techniques, heart pumping exercise and abdominal muscles strengthening showed relationship with p-value of 0.035. Conclusion: Relaxation techniques, heart pumping exercise and abdominal muscles strengthening are effective in reducing menstrual pain. Keyword: Decrease menstrual pain, relaxation techniques, exercise cardiac pump, strengthening abdominal muscles